Sistem Informasi Pembayaran SPP pada Sekolah di Kecamatan Gedung Tataan dengan Metode Extreme Programming - Rika Mersita; Dedi Darwis; Ade Surahman (Universitas Teknokrat Indonesia, 2022)
School financial administration is a step in managing school finances from acceptance to how the finances used are accounted for in an objective and systematic manner. Student financial administration systems in schools such as payment of tuition fees. SPP for schools in the Kelurahan Gedung Tataan still uses a manual process and has not been computerized. The system that runs the process of SPP payment transactions. The development of this system is carried out through several stages of data collection methods. The next stage is software development using the Extreme Programming method and using object-oriented PHP and MySQL programming applications including Unified Modeling Language (UML), as well as application testing using ISO 25010. Testing the application using ISO 25010 with a questionnaire filled out by 7 respondents on the web-based tuition payment system that has been built resulting in a total of 90% with the predicate Very Good, it is concluded that the system built has been considered feasible to be applied in managing tuition transactions in the building district arrangement.